2016
DOI: 10.2147/cpaa.s98221
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of daclizumab high-yield process with repeated administration of the clinical subcutaneous regimen in patients with relapsing-remitting multiple sclerosis

Abstract: BackgroundDaclizumab high-yield process (DAC HYP), a humanized immunoglobulin G1 monoclonal antibody specific for the α subunit (CD25) of the high-affinity interleukin-2 receptor, has demonstrated efficacy for treatment of relapsing forms of multiple sclerosis in Phase II and III clinical trials.ObjectiveTo characterize the pharmacokinetics (PK) of DAC HYP following repeated administration of the 150 mg subcutaneous (SC) dose every 4 weeks (q4wk), the proposed clinical regimen in patients with relapsing-remitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 4 publications
(9 reference statements)
1
16
0
Order By: Relevance
“…Pre-dose serum DAC HYP concentrations. The mean (SD) predose serum concentration of DAC HYP at the third dose was 16.5 (8.46) μg ml À1 , which is consistent with the previously characterized mean steady-state trough concentration of 14.9 (6.33) μg ml À1 following repeated dosing of DAC HYP 150 mg SC in patients with multiple sclerosis [16].…”
Section: Pharmacokineticssupporting
confidence: 88%
“…Pre-dose serum DAC HYP concentrations. The mean (SD) predose serum concentration of DAC HYP at the third dose was 16.5 (8.46) μg ml À1 , which is consistent with the previously characterized mean steady-state trough concentration of 14.9 (6.33) μg ml À1 following repeated dosing of DAC HYP 150 mg SC in patients with multiple sclerosis [16].…”
Section: Pharmacokineticssupporting
confidence: 88%
“…As we currently understand the effects of DAC in MS, the blockage of CD25 results in several changes [Wiendl and Gross, 2013;Bielekova et al 2011 Pharmacokinetics DAC HYP has characteristics of a typical immunoglobulin G, subclass 1 (IgG1) monoclonal antibody with slow absorption, linear PK at doses above 100 mg administered subcutaneously, high bioavailability, small volume distribution and slow clearance. Baseline CD25 levels, age and sex did not influence DAC HYP PK, and variability related to body weight does not seem to be clinically relevant [Diao et al 2016;Tran et al 2016].…”
Section: Mechanism Of Actionmentioning
confidence: 79%
“…It undergoes catabolism similar to that that of endogenous IgG proteins. Monthly (every 4 weeks) dosing resulted in achievement of steady state by the fourth dose [63]. Additionally, a larger study of 17,139 patients by Diao et al [64] demonstrated that the pharmacokinetics of DAC-β did not change with age, sex, or baseline T-cell (CD4+/CD25+) count.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The pharmacokinetics of DAC-β have been investigated in both healthy controls [62] and patients with MS, and were found to be similar in both populations [63,64]. DAC-β has a half-life of 21 days, and a median T max of 5 to 7 days.…”
Section: Pharmacokineticsmentioning
confidence: 99%